ALL-OPTICAL NETWORKS PERFORMANCE IMPROVEMENT BY SOLVING THE RWA PROBLEM USING GENETIC ALGORITHM - SAEED, MOHAMMED GHANIM; MUSTAFA, FIRAS MAHMOOD (Journal of Duhok University, 2021)
The problem of significant importance in the design of all-optical networks is the Routing and Wavelength Assignment (RWA) problem that depends on the light path route and wavelength using different algorithms. The main aim of (RWA) is to maximize the number of established connections. The significant indication by applying the RWA is to diminish the resources of the network demanded to serve the same number of requests. Consequently, the total number of requests served by the same resources will be increased. The main aim of this research is to manage the RWA algorithm by inspecting the performance of each algorithm in static (Fixed Routing Algorithm and Fixed Alternate Routing Algorithm) and dynamic routing algorithms in an optical network. With this work, the comparison between various RWA algorithms is performed using sorted shortest path algorithm and non-sorted random algorithm. Extra investigation and comparison can be achieved via the hiring Genetic algorithm (GA) as a tool to enhance optical network performance. The proposed techniques are applied to the design of some topologies depending on the number of nodes and the set of connecting links. With this work, it is assumed that all nodes are with no wavelength conversion and the identical load was utilized on the network by using three different algorithms. The comparison between the three algorithms shows that the dynamic algorithm gives good throughput and less resource usage. Besides, it has been shown that the shortest path algorithm yields results better than a random path algorithm. Finally, by using the GA tool in the optimization, the results have been obtained within the accepted rate.